MODIFIED CELL PENETRATING PEPTIDES FOR EFFICIENT POLYMER NANO/MICROPARTICLE DELIVERY FOR BONE DIFFERENTIATION APPLICATIONS - Jalal, Aveen (2020)
Nano/microparticle based gene therapy, the next generation of therapeutics could potentially cure inherited and acquired diseases through delivering nucleic acid intracellularly which otherwise are difficult to treat. Developing non-viral gene therapy vectors that both protect and deliver nucleic acid cargoes efficiently will be vital if gene augmentation and editing strategies are to be effectively combined with advanced regenerative medicine approaches. Currently, these methodologies utilise high concentrations of recombinant growth factors, which result in toxicity and off-target effects. Herein, the use of modified cell penetrating peptides (CPPs), termed Glycosaminoglycan (GAG) binding Enhanced Transduction (GET) with plasmid DNA (pDNA) encapsulated poly (lactic-co-glycolic acid) PLGA nano/microparticles (pDNA encapsulated PLGA NP/MPs) is demonstrated. In order to encapsulate the pDNA in PLGA NP/MPs, it was first condensed with several condensing agents such as high and low molecular weight cationic polypeptides and alcohol. Low molecular weight Poly L-Lysine (PLL) produced the smallest and most homogenous population of pDNA nanoparticles (pDNA NPs) in the range of 10-50 nm. These pDNA NPs were then encapsulated in PLGA MPs by double emulsion methods; yielding encapsulation efficiencies (EE) of ~ 30 %. pDNA encapsulated PLGA MPs were in the range of 0.35 µm in diameter with a negative surface charge. PLGA MPs complexed with GET peptides show enhanced intracellular delivery (up to seven folds) and transfection efficiencies (up to five orders of magnitude). Moreover, the pDNA cargo has enhanced protection from nucleases (i.e. DNase I) promoting their translatability.